The Effect of Audit Fee, Audit Opinion, KAP Size, Audit Tenure and Auditor Switching for Audit Delay in Companies on The Lq 45 Index Listed on Idx 2019-2021 - hanafi ardhi putra; Afrizal; Rahayu (Indonesian Journal of Economic & Management Sciences, 2023)
Examining the effects of audit fee, audit opinion, KAP size, audit tenure, and auditor switching on audit delay in firms on the LQ 45 index listed on IDX 2019–2021, this research looks at these factors and others. Companies on the LQ 45 index that listed on the IDX continuously from 2019 to 2021 make up the population of this study. Purposive sampling was the sampling method used to choose the 24 firms that satisfied the requirements. This study used a multiple linear regression analysis using SPSS 25. Audit fees and audit opinion were shown to significantly impact audit time in this research. However, audit time is not significantly affected by KAP size, audit duration, or auditor turnover